(untitled) (Fractal: Journal of Psychology, 2010)
We present the results generated with a sample of 704 professors of the forty graduate programs in the National Autonomous University of Mexico (UNAM), with the open question: Do you consider that it should exist a subject about professional ethics for all students?, With which contents?. The multiple answers were organized with two types of classification: three groups - "Answers not directly related to professional ethics", "Articulating values among general ethics and professional ethics" and "Answers directly related to professional ethics" - and the four knowledge areas in which the university organize the graduate studies: Physical and Mathematics Sciences and Engineering, Biological and Health Sciences, Social Sciences and Humanities and the Arts. The open question is part of a research project about professional ethics and of a questionnaire that includes other questions and an attitude scale about professional ethics.